7‐Ketocholesterol impairs phagocytosis and efferocytosis via dysregulation of phosphatidylinositol 4, 5‐bisphosphate. (10th June 2018) - Lu, Stella M.; Fairn, Gregory D.
Abstract : The plasma membrane is inhomogeneously organized containing both highly ordered and disordered nanodomains. 7‐Ketocholesterol (7KC), an oxysterol formed from the nonenzymatic oxidation of cholesterol, is a potent disruptor of membrane order. Importantly, 7KC is a component of oxidized low‐density lipoprotein and accumulates in macrophage and foam cells found in arterial plaques. Using a murine macrophage cell line, J774, we report that both IgG‐mediated and phosphatidylserine‐mediated phagocytic pathways are inhibited by the accumulation of 7KC. Examination of the well‐studied Fcγ receptor pathway revealed that the cell surface receptor abundance and ligand binding are unaltered while downstream signaling and activation of spleen tyrosine kinase is not affected. However, while the recruitment of phospholipase Cγ1 was unaffected its apparent enzymatic activity was compromised resulting in sustained phosphatidylinositol 4, 5‐bisphosphate [PtdIns(4, 5)P2 ] levels and polymerized actin at the base of the phagocytic cup. Additionally, we found that 7KC prevented the activation of PLCβ downstream of the P2Y6 G‐protein coupled receptor and that 7KC impaired PLCγ activity in response to a direct elevation of cytosolic calcium induced by ionomycin. Finally, we demonstrate that 7KC partly attenuates the activity of rapamycin recruitable constitutively active PLCβ3. Together, our results demonstrate that the accumulation of 7KC impairs macrophage function by altering PtdIns(4, 5)P2 catabolism and, thus, impairing actin depolymerization required for the completion of phagocytosis. Abstract : Cholesterol is an essential component of the plasma membrane and subject to oxidation. Oxysterols are known to influence immune cell function and contribute to atherosclerosis. At the molecular level, 7‐ketocholesterol (7KC) is a potent disruptor of membrane order and an inhibitor of phagocytosis. We demonstrate that 7KC impairs both phagocytosis and efferocytosis in macrophages by impairing phospholipase C activity. This sustains phosphatidylinositol 4, 5‐bisphosphate levels at the base of the forming phagosome thereby stabilizing the actin cytoskeleton and preventing pseudopod extension and particle internalization.